The Negative Impact of Mayantara Crime on the World Economy - Muhammad Hatta; Fittri Royani; Agus Maulizar; Herman Saputra; Darmansyah Darmansyah; Indra Gunawan; Marzuki Marzuki (International Journal of Law, Crime and Justice, 2025)
Cybercrime has become a serious threat to the stability of the world economy along with the increasing dependence on digital systems. The study analyzes the negative impact of cybercrime on the global economy, focusing on direct and indirect financial losses, disruptions to productivity and supply chains, and the implications of policies and mitigation efforts. The results of the study show that cybercrimes, such as ransomware, data theft, and phishing, cause significant financial losses to individuals, companies, and governments, and have an impact on consumer and investor confidence. In addition, cyberattacks on financial and industrial infrastructure disrupt business operations and exacerbate global economic inequality. Effective mitigation efforts involve strengthening cybersecurity regulations, investing in data protection technology, and increasing public awareness of the threat of cybercrime. With a deeper understanding of the economic impact of cybercrime, it is hoped that a more comprehensive strategy can be implemented to increase the resilience of the global economy against digital threats